The Effects of Learning Management by Using SQ4R Technique to Improve English Reading Comprehension Abilities of Eighth Graders - Jantabudsri, Chadaporn; Prasansaph, Dr. Soranabordin (Journal of Dhamma for Life, 2023)
The research were objectives to: 1) compare students’ English reading comprehension abilities before and after using SQ4R technique, and 2) study the students’ opinions towards using SQ4R technique. The sample, selected by a cluster sampling technique, comprised 29 eighth graders at Watnangsao School during the second semester of the academic year 2022. The instruments used for this research consisted of; 1) lesson plans with SQ4R technique 2) an English reading comprehension test used as a pretest and posttest; and 3) the opinions questionnaire towards using SQ4R technique. The paired-sample t-test was used to analyze the students’ English reading comprehension abilities. The results of the study were as follows: 1) The students’ reading comprehension abilities after using SQ4R technique were significantly higher at the 0.05 level. 2) The students’ opinions towards using SQ4R technique were at the highest level of agreement.